FRI0106 Changes in demographics and disease characteristics of patients in the united kingdom initiating adalimumab therapy for rheumatoid arthritis between 2003 and 2011. (23rd January 2014) - Brown, A. K.; Kirkham, B.; Lacerda, A.; McCaskill, R.; Howard, M.; Karunaratne, M.; Arora, V.
Abstract : Background: Recent advances in rheumatoid arthritis (RA) treatment strategies aim for early, tight control of disease activity to prevent permanent loss of function. Whether these advances have been accompanied by changes over time in patient (pt) characteristic patterns treated in clinical practice remains unknown. Objectives: The present analysis evaluated changes in pt demographics and disease characteristics over time in adult pts initiating adalimumab (ADA) therapy and a control group of patients initiating DMARDs in the United Kingdom (UK). Methods: Biologic-naïve pts registered through the British Society for Rheumatology Biologics Registry (BSRBR) between Sep 2003 and Dec 2011 who received their 1 st dose of ADA were included in this analysis. Based on registration date and receipt of 1 st dose, pts were categorized into groups of 2 years (Sep 2003-Dec 2005, Jan 2006-Dec 2007, on or after Jan 2008). Trends in baseline demographics or disease characteristics were assessed across the groups using Cochran-Armitage (categorical) or Jonckheere-Terpstra (continuous) tests. A control cohort, in which pts initiated standard DMARD therapy over the same time period, was used for comparative purposes. Results: Assessments of disease (DAS28 and HAQ-DI) declined significantly over time, however, both remained high at the time of ADA initiation. Mean disease duration before ADA initiation declined over time reflected in the significant increase in the proportion of pts with disease duration <5 or <2 years; however, mean disease duration remained high for the most recent group (11 years). Over time, significantly fewer DMARDs were used prior to ADA initiation, although the mean continued to exceed current UK guidelines (failure of 2 DMARDs) for all subgroups. A similar significant trend was observed in the control cohort, but this group of pts received 1 fewer DMARD than the ADA cohort on average prior to registration. While the proportion of pts in the ADA cohort receiving DMARD therapy at baseline increased over time, the proportion requiring corticosteroids declined across the 3 subgroups. Image/graph: Conclusions: The pattern of disease characteristics of RA pts in the UK initiating ADA therapy from 2003 to 2011 shifted in favor of earlier intervention and less prior DMARD exposure. Despite these changes, disease activity and disability remained high. While these data may be reflective of loss of previous DMARD control, they also emphasize the need for increased compliance with UK treatment guidelines. Acknowledgements: AbbVie is a co-sponsor of the BSRBR. AbbVie participated in the analysis and interpretation of the data, and in the writing, reviewing, and approval of the final version of the abstract. Medical writing support was provided by Benjamin Wolfe, PhD, and Douglas E. Dylla, PhD of AbbVie Inc. Disclosure of Interest: A. Brown Grant/research support from: AbbVie, Pfizer, MSD, UCB, Roche, Servier, and Menarini, Consultant for: AbbVie, Pfizer, MSD, UCB, Roche, Servier, and Menarini, Speakers bureau: AbbVie, Pfizer, MSD, UCB, Roche, Servier, and Menarini, B. Kirkham Grant/research support from: AbbVie, BMS, Chugai, Pfizer, Roche, and UCB Pharma, A. Lacerda Shareholder of: AbbVie, Employee of: AbbVie, R. McCaskill Shareholder of: AbbVie, Employee of: AbbVie, M. Howard Shareholder of: AbbVie, Employee of: AbbVie, M. Karunaratne Shareholder of: AbbVie, Employee of: AbbVie, V. Arora Shareholder of: AbbVie, Employee of: AbbVie